(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
From 1947 until 1977, West Bengal’s students were active participants in the state’s social andeconomic developments. As a newly formed state, West Bengal was confronted with a slew of challenges,including political unrest, economic stagnation, migration issues, a food shortage, the Naxalite uprising,the Indo-Chinese, Indo-Pak, and Bangladesh Liberation War, as well as widespread unemployment. At thistime, students in Bengal were drawn to the spontaneous public protests and joined such activities for thecause of nation building. Not only did the student movement flourish in the Modern Age, but it alsoappeared in bits and pieces throughout the ancient and medieval periods. It was first welcomed by theeducated elite, but their skepticism quickly turned to disapproval, and they pushed for greater workprospects for Indians, as well as greater freedom of expression and organization. Students’ involvementin West Bengal’s popular movements was one of history’s most extraordinary moments.